Employee Well-being in the Spotlight: The Role of HR in Mental Health Support - Ridwan Hakiki; Hendrik Pandiangan; Dendi Zainuddin Hamidi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the intricate relationship between Human Resources (HR) practices, mental health support, employee engagement, and employee welfare within PT. Ekadharma International, Tbk's Pontianak branch. Through a sample of 65 employees, data was collected and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis. The results indicate a significant direct relationship between HR practices and employee engagement, as well as between HR practices and employee welfare. However, the direct relationship between mental health support and employee engagement was found to be non-significant. Despite this, both HR practices and mental health support were indirectly linked to employee welfare through employee engagement. These findings underscore the critical role of HR practices in fostering employee engagement and welfare, while highlighting the importance of integrating mental health support initiatives with strategies aimed at promoting employee engagement. The implications of these findings are discussed in terms of enhancing organizational performance and employee well-being within PT. Ekadharma International, Tbk's Pontianak branch.